Correlações entre passes, finalizações, consumo de oxigênio máximo e padrão de sono em jogadoras de futsal - SILVA, Diogo Matheus Barros da (2021)
Aim: To verify the correlation between technical ability, tactic, physiological capacity (VO2), and (sleep) in female futsal players. Materials and Methods: The sample consisted of 10 indoor futsal players with the following characteristics: average age in years of 26.50 ±4.70, height in meters of 1.61 ±0.06, body mass in kg 54.83 ±8.51, body mass index 21.08 ±2.67, fat percentage (%G) 20.63 ±9.12, with experience time over 3 years, 50% schooling in the incomplete higher education, different socioeconomic profiles. Passing and finishing skills were analyzed by performance analysis throught video; the submaximal progressive incremental test was performed to identify the maximum oxygen consumption (maximum VO2); questionnaires were applied to characterize the sample: GPEFF for aspects of time, duration, frequency of training, and schooling, ABEP for socioeconomic stratification; Sleep patterns were used: MEQ-SA for chronotype, ESS-BR for excessive daytime sleepiness, and PSQI-BR for subjective sleep quality. Results: It was observed the values, in the 1st game, between the players, for a minimum pass (0) and a maximum pass (48), a minimum pass (1) and a maximum pass (12), a correct shooting (0), a wrong shooting minimum (0) and maximum (10), in the 2nd game for minimum (0) and maximum (49) pass, minimum (0) and maximum (10) wrong pass, minimum (0) and maximum (1) , minimum (0) and maximum (5) wrong shooting, in the 3rd game for minimum (0) and maximum (37) right pass, minimum (0) and maximum (14) wrong pass, correct (0), wrong shooting minimum (0) and maximum (4); for maximum oxygen consumption, it presented minimum (46) and maximum (83) ml.kg.min, chronotype minimum (43) and maximum (60), minimum (6) and maximum (14) drowsiness, subjective quality of sleep minimum (7) and maximum (9); finding weak correlations between abilities with capacity, abilities and sleep, sleep variables, capacity and sleep. However, there is a moderate correlation between chronotype (sleep) and VO2 (capacity) and chronotype (sleep) with correct shooting (skill). Conclusion: Players present a pass and shooting with greater use of correct passes in relation to the correct finishes, the maximum oxygen consumption as superior / excellent, as for the characteristic of the sleep pattern, the prevalence of the intermediate chronotype over the morning was observed, as well as of light drowsiness under absence of drowsiness, in addition to the higher prevalence of poor sleep quality, which may impact sports performance. As well as correlations between variables of abilities, capacty and sleep.